ACCOUNTING OF TRANSACTION COSTS OF A FIRM - T. N. Lebedeva (Дискурс, 2018)
Types, classification and features of transaction costs are considered, and the classification of transaction costs during business processes, specifically the processes of supply, production and sales, is presented. The dynamics of transaction costs of the organization depending on the stages of its life cycle is shown. The problems associated with the assessment and accounting for transaction costs are identified. The existing methods of transaction costs accounting are presented. Accounts which reflect transaction costs are considered. A method of accounting for transaction costs in money (explicit costs) on a distinct account is proposed. It is proposed to keep implicit transaction costs associated with the loss of time segregated on a separate off-balance sheet account. The features of management accounting of transaction costs are presented.